SOSIALISASI JARINGAN GAS PERKOTAAN BAGI MASYARAKAT - Ristawati, Arinda; Prima, Andry; Yulia, Prayang Sunny; Kurniawati, Riskaviana; Puspitosari, Meldinar Riska; Fattahanisa, Aqlyna; Wijayanti, Puri; Aryanto, Reza (Universitas Trisakti, 2023)
Socialization of the utilizations and advantages of city gas is a community service that aims to make people understand the growth of the urban gas distribution sector in Indonesia and provide information to the public about LPG substitute economic energy sources. Gas network for households means distributing gas through pipes to households. The limited availability of household gas in DKI Jakarta made this socialization theme raised. The location chosen is the Tanjung Gedong area, Tomang-sub distrct, Grogol Petamburan district, West Jakarta, which in this case, the area is a densely populated area, especially family settlements. The participants who took part in this community service were housewives. The method used is to provide socialization about the urban gas network developed by the government for household gas purposes, the socialization is carried out online with the zoom facility and some others offline in the community while still using the existing health protocol. The result of this community service activity is that the public is able to recognize and understand the existence of a gas network whose infrastructure development is being developed by the government through PT PGN Tbk. This community service makes the community clearly aware of the flow in the “jargas” development program.